2017
DOI: 10.5604/12321966.1235181
|View full text |Cite
|
Sign up to set email alerts
|

The quality of life and satisfaction with life of women who are childless by choice

Abstract: Objective. The study attempts to identify and analyze factors affecting the quality of life and satisfaction with life of women who are childless by choice. Materials and method. The research instruments used were: the WHOQOL-Bref questionnaire and the Satisfaction with Life Scale (SWLS), and author's own questionnaire. Results. A better overall quality of life, perception of own health and quality of life in all the specific domains analyzed was found among childless women living in cities, college/university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Harris et al (2016) demonstrated that SwL in young Iranian women was determined by their income, living conditions, age, marital status, ethnicity, education, and religious attitudes [ 12 ]. Bień et al (2017) studied women who were childless by choice, and demonstrated that their SwL was determined by such socio-demographic factors as age, residence, education, marital status, and financial standing [ 43 ]. Socio-economic standing, which comprises income, education, and living conditions, is a significant determinant of SwL, as reported in SwL studies by Abbott & Sapsford (2006) in Russians and Ukrainians, Jan & Masood (2008) in women, Harris et al (2016) in young Iranian women, and Bień et al (2017) in women who decided to remain childless [ 12 , 40 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Harris et al (2016) demonstrated that SwL in young Iranian women was determined by their income, living conditions, age, marital status, ethnicity, education, and religious attitudes [ 12 ]. Bień et al (2017) studied women who were childless by choice, and demonstrated that their SwL was determined by such socio-demographic factors as age, residence, education, marital status, and financial standing [ 43 ]. Socio-economic standing, which comprises income, education, and living conditions, is a significant determinant of SwL, as reported in SwL studies by Abbott & Sapsford (2006) in Russians and Ukrainians, Jan & Masood (2008) in women, Harris et al (2016) in young Iranian women, and Bień et al (2017) in women who decided to remain childless [ 12 , 40 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, infertile women had higher quality of life scores than women who had children. This may be surprising at standing predicted better quality of life 23 . In a study performed in American population, it was found that childless individuals earned more and accumulated more wealth than those who had children 24 .…”
Section: Discussionmentioning
confidence: 97%
“…Another study [22], identified BMI, time from diagnosis, having children and socio-economic status as determinants of satisfaction with life. Bień et al [23] found satisfaction with life among childless women to be affected by age,place of residence, education, marital status and financial standing. The present findings are consistent with the above, as satisfaction with life among women of reproductive age was associated with their age, education, and marital status.…”
Section: Discussionmentioning
confidence: 99%